Corn Using Efficiency Analysis in Labuhan Ratu IV Village, Labuhan Ratu District, East Lampung Regency, Lampung - Dindy Darmawati Putri; Aji Setiawan; Lutfi Zulkifli (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
One of the essential food crops worldwide is corn, which is also utilized in Indonesia as a feed for animals, a raw material for industry, and a source of basic requirements. This study intends to: (1) know the costs and income; and (2) know the efficiency of farming. In Labuhan Ratu IV Village, Labuhan Ratu District, East Lampung Regency, the study's location was purposefully chosen. Cost and Revenue Analysis, Revenue Cost Ratio was utilized to analyze the study's data. (1) The average cost was 8.093.897,00 IDR, while the average income was 16.896.017,00 IDR, according to the findings. (1) Corn cultivation has been effective or profitable, as indicated by an R/C ratio of 2,09; (2) The average profit obtained is 8.802.119,00 IDR.